Effect of urea on warfarin-human serum albumin complex: fluorscence study / Nasim Sakhaei - Sakhaei, Nasim (2011)
In order to evaluate the change in the drug binding ability of human serum albumin (HSA) with the alteration in its native conformation, effect of urea was investigated on the tertiary structure of HSA as well as on its interaction with warfarin, an anticoagulant drug, using fluorescence spectroscopy. Such studies are important from the physiological point of view as alteration in the drug binding capacity of HSA has been noted in several diseases. Both intrinsic fluorescence and tryptophan (Trp) fluorescence were used to monitor these urea-induced changes upon excitation at 280 and 295nm respectively. Fluorescence spectra of native HSA were characterized by the presence of an emission maximum around 339 and 343nm when excited at 280 and 295nm respectively. Incubation of protein with increasing urea concentrations for 12 hours produced a significant decrease in the fluorescence intensity and an initial small blue shift followed by a marked red shift in the emission maximum. In addition to these characteristics, peak splitting was also observed at higher urea concentrations upon excitation at 280nm, which was absent upon excitation at 295nm. Reducing the incubation time with urea from 12 hours to 60 minutes did not significantly affect these characteristics. Urea transition curve showed a two-step, three-state transition with accumulation of an intermediate around 5.2